The impact of crop year and certain agrotechnical factors on maize yield - Becze, Zsófia (Acta Agraria Debreceniensis, 2013)
The experiment was set up with eight maize hybrids with different genetic characteristics in 2012. In our study were included hybrids with different length of growing season. We studied the effect of NKP fertilization and plant density on the yield. Comparing to controll treatment it was found that highest yield was at N40+PK treatment. It was three times higher than agro-ecological optimum. Due to the droughty year the effect of plant density it was minimum. The development rate in case of sowing date I. and II. showed an almost identical picture in the scope of the sowing date trial. However, hybrids with excellent adaptability were capable of a yield above average even in this extreme year.